Determinants and Trends of the Use of Intravenous Thrombolysis for Minor Stroke: A Population-Based Study, 2016 to 2020. Issue 11 (10th August 2022) - Font, Maria Àngels; García-Sánchez, Sonia María; Mengual, Juan José; Mena, Luis; Avellaneda, Carla; Serena, Joaquín; Valls-Carbó, Adrián; Chamorro, Ángel; Ustrell, Xavier; Molina, Carlos; Cardona, Pere; Guasch-Jiménez, Marina; et al.
Abstract : Background: We analyzed the main factors associated with intravenous thrombolysis (IVT) in patients with minor ischemic stroke. Methods: Data were obtained from a prospective, government-mandated, population-based registry of stroke code patients in Catalonia (6 Comprehensive Stroke Centers, 8 Primary Stroke Centers, and 14 TeleStroke Centers). We selected patients diagnosed with ischemic stroke and National Institutes of Health Stroke Scale (NIHSS) ≤5 at hospital admission from January 2016 to December 2020. We excluded patients with a baseline modified Rankin Scale score of ≥3, absolute contraindication for IVT, unknown stroke onset, or admitted to hospital beyond 4.5 after stroke onset. The main outcome was treatment with IVT. We performed univariable and binary logistic regression analyses to identify the most important factors associated with IVT. Results: We included 2975 code strokes; 1433 (48.2%) received IVT of which 30 (2.1%) had a symptomatic hemorrhagic transformation. Patients treated with IVT as compared to patients who did not receive IVT were more frequently women, had higher NIHSS, arrived earlier to hospital, were admitted to a Comprehensive Stroke Centers, and had large vessel occlusion. After binary logistic regression, NIHSS score 4 to 5 (odds ratio, 40.62 [95% CI, 31.73–57.22]; P <0.001) and large vessel occlusion (odds ratio, 16.39 [95% CI, 7.25–37.04]; P <0.001) were the strongest predictors of IVT. Younger age, female sex, baseline modified Rankin Scale score of 0, earlier arrival to hospital (<120 minutes after stroke onset), and the type of stroke center were also independently associated with IVT. The weight of large vessel occlusion on IVT was higher in patients with lower NIHSS. Conclusions: Minor stroke female patients, with higher NIHSS, arriving earlier to the hospital, presenting with large vessel occlusion and admitted to a Comprehensive Stroke Centers were more likely to receive intravenous thrombolysis.